Leiomyoma in the Retzius space - Sikora-Szczęśniak, Dobrosława (Menopause Review/Przegląd Menopauzalny, 2016)
Parauterine location of leiomyomas is observed to be an extremely rare clinical condition. However, when benign or malignant primary tumours are detected in that area, they are often found in the Retzius space. There have been only six cases of leiomyomas in the Retzius space reported in the literature so far. The paper presents one such leiomyoma case located in the Retzius space. This extremely rare location of the tumour justifies its presentation. The medical records of the patient treated in the outpatient’s obstetrics and gynaecology (ob-gyn) clinic, her case history, and hospital records, supplemented by information obtained from the patient’s daughter, were analysed. The patient, a 50-year-old woman with type 2 diabetes, was referred to hospital for diagnosed secondary anaemia due to heavy menstruation for four months, which was associated with intramural leiomyoma in the anterior wall of the uterine body. Clinical examination found a large leiomyoma located in the anterior wall of the uterus. Laparotomy was performed: apart from and a leiomyoma in the uterine body it found a tumour, 140 × 100 mm in size, in the Retzius space. Total resection of the tumour was performed. Since the leiomyoma was located in the uterine wall, hysterectomy with bilateral excision of adnexa was also performed. The patient was discharged home in generally good condition on the sixth day following the operation. Concomitant occurrence of leiomyoma atypically located in the Retzius space and leiomyoma in the uterine body made perioperative diagnosis very difficult.